Conservation of goose genetic resources in Poland - past and present status. Issue 3 (1st September 2019) - Dobrzański, J.; Calik, J.; Krawczyk, J.; Szwaczkowski, T.
Abstract : Conservation of animal genetic resources is considered as one of the main challenges of today's breeding. Every breed of livestock is a valuable element of the world's animal genetic diversity. Over the last few decades, considerable reductions in the number of local breeds and their sizes have been registered. This trend caused the need to implement conservation programmes for endangered goose species. Poland has a number of local goose breeds which are the achievements of many generations of breeders. The objective of this review was to present the current status of the realised conservation programmes for 14 goose breeds in Poland by analysing population and molecular parameters. The conservation status of these populations has been presented including the effective population sizes, hypothetical inbreeding level, trends in performance traits as well as parameters estimated on the basis of genetic markers. In all the cases population sizes were well over 100 individuals, which is the minimum recommended by the FAO for conservation flocks. The effective population size ranged from 179 to 452, affecting a relatively low inbreeding level from 0.1 to 0.74%. The estimated correlations between hypothetical inbreeding rates and reproduction traits were negative. The heterozygosity coefficients varied from 0.27 (Biłgorajska breed) to 0.55 (Garbonosa breed). Generally, the parameters for goose breeds in Poland were compatible with the recommendations of the FAO.